EIB Working Paper 2021/03 - Assessing climate change risks at the country level the EIB scoring model - Ferrazzi, Matteo (European Investment Bank, 2021)
The EIB Climate Change Risk Country Scoring Model provides a way to comprehensively assess the climate change risks faced by more than 180 countries. The two sets of scores for physical and transition risks aggregate exposures to various risk factors, taking into account the adaptation and mitigation capacity of each country. The scores confirm that climate risk is a relevant challenge for all countries. However, low-income economies are more vulnerable to physical risk - in particular to acute events, rising sea levels and excessive heat - and in parallel have lower ability to mitigate the challenges posed by the energy transition. High-income economies generally face higher risks from the transition to a low-carbon future. Countries more dependent on fossil fuel revenues are also among the most exposed to transition risk. This paper provides insights into the model as it is currently being developed. Understanding the relative climate risks faced by countries support the management of climate risks at the country level, as well as helping to understand the environmental and policy conditions faced by firms in each country. It can also help to identify mitigation and adaptation priorities and related financing needs. Taken together, a better understanding of the risks and the consequent adaptation and mitigation needs will help to ensure that opportunities to enhance climate resilience are not missed.